Moral panics or monstrous offenders?: balancing public perceptions of sexual offenders with their offence patterns - Wynn, Chelsea (2018)
This thesis aims to provide a broad overview of contemporary challenges in relation to sexual offending, with specific focus being placed on the need to balance the public’s perceptions of those convicted of sexual offences with the reality of their offence patterns, to determine what risk society really faces from these individuals. In doing this, it incorporates diverse methods, including a systematic review, an empirical research study, an individual case study and a critique of a psychometric measure. Following a general introduction in Chapter 1, Chapter 2 presents a systematic evaluation of 13 studies investigating public perceptions of sexual offenders, with specific focus on comparing public demographic variables as predictors of these attitudes. It was found that overall; the public’s perceptions were negative, with beliefs about high recidivism rates amongst other misperceptions. Demographic characteristics were shown to be inconsistent in predicting punitive judgments. Level of educational attainment was the only demographic variable investigated that was consistently associated, with higher levels of education resulting in more positive perceptions. In Chapter 3, the offence patterns of repeat sexual offenders are investigated, including an analysis of whether this population escalate, de-escalate or remain stable over time. The results indicate an overall pattern of stability, indicating that sexual recidivists commit the same category of offence from one offence to the next. However, escalation was also common, a finding that warrants further exploration. Chapter 4 explores the factors that contribute to the onset and escalation of the offence behaviours of a repeat sexual offender, through the use of psychological formulation. Results indicated that a different set of risk factors contributed to the onset of the client’s offending compared to those that contributed to escalation. Chapter 5 evaluates the Community Attitudes Toward Sex Offenders (CATSO) scale (Church, Wakeman, Miller, Clements, & Sun, 2008), an assessment measure used in Chapter 2. Finally, Chapter 6 provides a discussion and conclusion to the thesis, drawing together the implications of the research.